Pressure-promoted highly-ordered Fe-doped-Ni2B for effective oxygen evolution reaction and overall water splitting. Issue 10 (17th February 2021) - Tian, Ruifeng; Zhao, Shijing; Li, Junkai; Chen, Zhibin; Peng, Wenfeng; He, Yan; Zhang, Lili; Yan, Shuai; Wu, Lailei; Ahuja, Rajeev; Gou, Huiyang
Abstract : Accurate doping at special atomic sites can achieve effective control of active centers for the oxygen evolution reaction (OER), leading to the synthesis of active intermediates with higher conversion efficiency. Abstract : Accurate doping at special atomic sites can achieve effective control of active centers for the oxygen evolution reaction (OER), leading to the synthesis of active intermediates with higher conversion efficiency. Here we report the successful doping of Ni2 B with Fe/Co to form highly ordered FeNiB and CoNiB electrocatalysts with a tetragonal Ni2 B structure. A highly crystalline FeNiB electrode is found to have a very low polarization overpotential of 257 mV for the OER and a water splitting potential of 1.54 V at a current density of 10 mA cm −2 . XRD refinement, XPS and XAFS characterization found that doping with iron leads to the weakening of the bond strength of TM–B, which facilitates the adsorption of oxygen. During the OER process, the increasing dissolution of boron oxides promotes the effective exposure of metal active centers and boosts the catalytic performance. Theoretical calculations reveal that the substitution of Fe atoms in Ni2 B make its DOS near the Fermi level higher by 2.78 times compared to that of the original Ni2 B, which helps to increase the electronic conductivity and the catalytic performance.